On the formation of magmatic sulphide systems in the lower crust by long‐lived mass transfer through the lithosphere: Insights from the Valmaggia pipe, Ivrea Verbano Zone, Italy. (1st October 2020) - Locmelis, Marek; Moroni, Marilena; Denyszyn, Steven W.; Webb, Laura E.; Fiorentini, Marco L.; Sessa, Gianluca; Caruso, Stefano; Mathur, Ryan; Nanzad, Bolorchimeg
Abstract: The lower crustal domain of the Ivrea‐Verbano Zone (NW Italy) hosts five 300‐m‐wide pipe‐like ultramafic intrusions that are metasomatized and exhibit Ni‐Cu‐PGE sulphide mineralization. To better constrain the role of metasomatism in the ore genesis, we studied the best‐preserved pipe at Valmaggia which was emplaced 249 Myrs ago. Phlogopite 40 Ar/ 39 Ar analyses show that the pipe was infiltrated by metasomatic fluids derived from the subcontinental lithospheric mantle (SCLM) in two pulses at 208 Ma and 189 Ma which introduced sulphides into the pipe. Consequently, the pipe repeatedly acted as a preferred path for mass transfer from the SCLM into the lower crust over >60 Myrs (i.e., emplacement to second metasomatic pulse). Uplifted block margins, such as the Ivrea‐Verbano Zone, are potentially important exploration targets for magmatic sulphides. We argue that exploration strategies should focus on structures such as pipes that can focus metasomatic agents during ascent through the lithosphere.